Age, Sex, and Symptom-Dependent Variations in Total IgE and Eosinophils in Atopic Patients: A Five-Year Retrospective Study - Zhao L; Wu Y; Zhu H; Lin Y; Su H; Hu J; Zhang M; Bao W (Journal of Asthma and Allergy)
Lei Zhao,* Yiting Wu,* Hui Zhu,* Yanmei Lin, Hang Su, Jingwei Hu, Min Zhang, Wuping Bao Department of Respiratory and Critical Care Medicine, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wuping Bao, Department of Respiratory and Critical Care Medicine, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, NO. 100 haining Road, Hongkou District, Shanghai, 200080, People’s Republic of China, Tel +0086 21 63240090 3091, Email wupingbao1982@163.com Min Zhang, Department of Respiratory and Critical Care Medicine, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, NO. 100 haining Road, Hongkou District, Shanghai, 200080, People’s Republic of China, Email zhangmin@sjtu.edu.cnBackground: Total immunoglobulin E (t-IgE) and eosinophils as central effector molecular and cells are crucial biomarkers for allergic diseases. Age, sex and allergic symptoms may influence these biomarkers and the relationship among t-IgE, eosinophils, and atopic diseases remained unknown.Methods: A five-year retrospective study enrolled 7654 patients with allergic symptoms underwent allergen testing. We collected age, sex, symptoms, and complete blood counts and explored variations in t-IgE and eosinophil across demographic and clinical parameters.Results: Among atopic patients, t-IgE levels peaked in children, decreasing with age, with a slight increase in the elderly, mirroring eosinophil trends. Females consistently exhibited lower t-IgE and eosinophil levels than males, regardless of atopic status. High t-IgE and eosinophils were the most common in patients ≥ 12 years with respiratory symptoms. Dust mites often caused respiratory symptoms. Egg allergies typically affected the ear, nose, and throat (ENT). Seafood/peanut allergies were linked to skin symptoms. Interestingly, elevated t-IgE and eosinophil levels did not consistently correlate with positive allergen tests. Among atopic patients, 44.5% exhibited normal t-IgE, and 41.4% had normal eosinophils. In the subgroup (22.8%) with both markers normal, more were females (62.5%). Sensitization to allergens like soy, shrimp, mold combination, Artemisia argyi, common ragweed, and willow/aspen/elm may fail to elevate t-IgE and eosinophils.Conclusion: Characteristics such as older age, female, skin and ENT symptoms, and allergens may correlate with lower t-IgE and eosinophils in the allergic populations which means we should pay more attention to these population, even if their t-IgE and eosinophils are normal, the allergen test is necessary for treatment strategies.Clinical Trial Registration: ChiCTR2300067700 (Date of Registration: 2023– 01-18).Keywords: atopy, IgE, eosinophil, age, sex